2019
DOI: 10.2298/jsc180810025w
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidation of sulfamethoxazole using Ti/SnO2-Sb/Co-PbO2 electrode through ANN-PSO

Abstract: Even in a trace amounts, the presence of antibiotics in aqueous solution is getting more and more attention. Accordingly, appropriate technologies are needed to efficiently remove these compounds from aqueous environments. In this study, we have examined the electrochemical oxidation (EO) of sulfamethoxazole (SMX) on a Co modified PbO 2 electrode. The process of EO of SMX in aqueous solution followed the pseudo-first-order kinetics, and the removal efficiency of SMX reached the maximum value of 95.1 % within 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is one of many antibiotics [2]. A survey of the literature showed that different techniques have been reported for SMZ analysis, some of which include spectrophotometric methods [1], for instance, HPLC [3], electrochemical methods [4] an solid phase extraction [5]. Diazotization method is simple and inexpensive method.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of many antibiotics [2]. A survey of the literature showed that different techniques have been reported for SMZ analysis, some of which include spectrophotometric methods [1], for instance, HPLC [3], electrochemical methods [4] an solid phase extraction [5]. Diazotization method is simple and inexpensive method.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complications associated with the relationship of the above-mentioned parameters, it is difficult to explain the accurate relationship between these parameters. On the other hand, it is costly and time-consuming to study different conditions and obtain sufficient experimental data that encompasses most conditions (Wan et al, 2019). Thus, modeling and optimization of wastewater treatment processes utilizing artificial intelligence (AI) due to their unique advantages (like a low number of parameters, low computation time and no need for boundary and initial condition), with a focus on achieving the maximum removal efficiency of various pollutants, especially dye pollutants, has received much attention (Fan et al, 2018;Mossavi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This risk renders it necessary to determine the SMZ content in pharmaceutical formulations as well as to test residues of SMZ, which should not exceed the regulatory limit in drinking water or in food originating from animals, such as eggs, milk, and meat [5]. Therefore, various SMZ detection methods including spectrophotometry [6], electrochemical methods [7,8], LC/MS [9], HPLC [10,11], solid-phase extraction [12], and voltammetry [13] have been developed.…”
Section: Introductionmentioning
confidence: 99%